2020
DOI: 10.9734/irjpac/2020/v21i1530253
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Biochar on Agriculture and Environments

Abstract: Crop residue management becomes the challenging issue to farmers for balancing between the economic and sustainable environment. Though burning is the easiest way of destroying the crop waste it not only causes drastic changes in green house gas but also large amount of nutrients are removed from soil by plants. Hence the technique which protects the environment along with enhancing soil quality is needed. Therefore pyrolysis of crop residue can become an alternate technique against past strategies. The hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…Pyrolysis is a popular technology used for managing waste, which sets itself apart by being able to generate gaseous, liquid, and biochar products [13]. This thermochemical process decomposes biomass in the absence of oxygen to produce biochar [14,15]. According to research reported elsewhere, the temperature range for slow pyrolysis of biomass is typically between 300 and 800 • C [16][17][18], but recent studies suggest that it can range from 300 to 950 • C [19].…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolysis is a popular technology used for managing waste, which sets itself apart by being able to generate gaseous, liquid, and biochar products [13]. This thermochemical process decomposes biomass in the absence of oxygen to produce biochar [14,15]. According to research reported elsewhere, the temperature range for slow pyrolysis of biomass is typically between 300 and 800 • C [16][17][18], but recent studies suggest that it can range from 300 to 950 • C [19].…”
Section: Introductionmentioning
confidence: 99%
“…Biochar allows carbon fixation for at least several decades as it can function as a permanent carbon sink and hence can be used to tackle climate change. The emission of thousands of tons of CO 2 into the atmosphere can be reduced if the emitted carbon from fires can be transformed into biochar [12]. Moreover, biochar exhibits adsorbent properties, which can improve soil properties [13][14][15] and promote water retention [16,17].…”
Section: Introductionmentioning
confidence: 99%